Program-Technical Aspects of Encryption Protection of Users' Data - Логінова, Наталія Іванівна; Логинова, Наталья Ивановна; Loginova, Natalia I.; Трофименко, Олена Григорівна; Трофименко, Елена Григорьевна; Trofimenko, Elena G.; Задерейко, Олександр Владиславович; Задерейко, Александр Владиславович; Olexander Zadereyko, Olexandr V.; Чанишев, Рашид Ібрагимович; Чанишев, Рашид Ибрагимович; Chanyshev, Rashid I. (My University, 2016)
The effective protection of different storage devices is impossible without multifunctional encryption software. For this task solution it is suggested to use TrueCrypt, the crossplatform cryptographic software, allowing to carry out the on-the-fly encryption. There was conducted the analysis of TrueCrypt performance capabilities and efficiency. The algorithm of TrueCrypt practical application for storage device protection was worked out. It was shown that TrueCrypt implementation is the most effective measure which allows to prevent the losses of users' confidential information stored on PC as well as on removable storage devices.
Loginova N. Program-Technical Aspects of Encryption Protection of Users' Data / Natalia Loginova, Elena Trofimenko, Olexander Zadereyko, Rashid Chanyshev // Modern Problems of Radio Engineering, Telecommunications, and Computer Science : XIIIth 2016 International Conference (Lviv-Slavsko, February 23 – 26, 2016). - Lviv, 2016. - p. 443 -445. = Сучасні проблеми радіоелектроніки, телекомунікацій, комп'ютерної інженерії : матеріали Міжнар. конф.TCSET’2016 ( Львів-Славсько, 23-26 лютого 2016 р.). - Львів, 2016. - с. 443-445.
Keywords: information security; TrueCrypt; cryptocontainer; information protection; data protection; removable storage device; on-the-fly encryption; інформаційна безпека; криптоконтейнер; захист інформації; захист даних; знімний запам'ятовуючий пристрій; оперативне шифрування; информационная безопасность; криптоконтейнер; защита информации; защита данных; съемное запоминающее устройство; оперативное шифрование